Comprehensive Look at Blood Transfusion Utilization in Total Joint Arthroplasty at a Single Academic Medical Center under a Single Surgeon. (16th July 2013) - Robinson, Sean; McGonigle, Owen; Volin, Sam; Sun, Yung-Chi; Moore, Matthew; Cassidy, Charles; Smith, Eric
Abstract : The utilization of autologous and allogeneic transfusions in total joint arthroplasties was to characterize patients who may benefit from giving preoperative blood donations. We conducted a retrospective chart review of 525 patients to document preoperative hematocrit, estimated blood loss, length of stay, transfusions, and medical comorbidities. Results of our review showed that total hip arthroplasty revision (THA-R) had the highest prevalence of transfusions (60%) followed by total hip arthroplasty (THA, 53%), total knee arthroplasty-revision (TKA-R, 33%), and total knee arthroplasty (TKA, 23%). There was significant waste of autologous donations: 92% of TKA patients, 64% of THA, and 33% of THA-R patients wasted on average 1.527, 1.321, and 1.5 autologous units, respectively. Pre-operative hematocrit was the strongest predictor of future transfusion need across all procedures, and primary THA had additional predictors in age and gender.